Population Density and Susceptibility of Some Varieties of Potato to Infested by Aphid and Thrips on Spring Plantation in the Middle of Iraq (Baghdad Science Journal, 2016)
Aphid Aphis spp (Hemiptera:Aphididae) and Thrips Thrips spp (Thysanoptera: Thripidae) an economically important pests on several crops in the world and Iraq, that transfer many viruses diseases to it. Field studies were conducted to assessment the population density of these insects and susceptibility of six varieties (Barin, Revera, Divela, Rudlph, Alazata and Pleny) to infestation during 2013 spring season. The results were showed that all Potato varieties were infested by Aphis and Thrips on spring plantation but with different percentage. The Divela variety was higher percentage of infestation and high population density of aphid which averaged 1.47 insect/ leaf while in Alazata was the lower population density which averaged 1.02 insect/ leaf .The higher population density of thrips was recorded on Revera variety with average 2.44 insect / leaf while the lower population density was recorded on Alazata with average 1.61 insect / leaf. The results also showed that the population density of both insect were high at the beginning of the season, reaching 5 insect /leaf for aphid and 6 insect / leaf for thrips in the season half of February,which coincided with emergence of the plants and the beginning of vegetation growth. Different susceptibility were found between varieties to infested by Aphis and Thrips on spring plantation in middle of Iraq.